An insight on initiation of same sex behavior among men who have sex with men in Agra district of India: A Qualitative study - Aqeel Khan , Iqbal; Chaudhary, Shailendra Singh; Misra, Sunil Kumar; Geetu Singh,; Singh, Tej Pal; Royal , Abhishek (Indian Journal of Community Health, 2020)
Background: Men who have sex with men (MSM) refer to all males (of any age) who engage in sexual relations with other males. The gross stigmatization and discrimination of homosexuals have affected the life and health of MSM. Aims & objective: To get an insight on circumstances of initiation and continuation of same sex behavior among MSM. Material & Methods: This qualitative study was conducted in MSM population in Agra district in India. Audio recorded in-depth interviews were transcribed into verbatim. Potential themes were extracted as a part of analysis as per relevant experiences of the participants. Data saturation achieved after 13 In-depth interviews. Results: The initiation of same sex behavior among MSM was at a young age and was mostly without their consent. Almost all participants were below the legal age of giving consent for sex and their first homosexual partner was a familiar, elderly in position of authority. They played a passive role in their initial sexual encounter and none of them was able to discuss it freely with their family members or friends. They mostly felt depressed after their first homosexual encounter. They had continued this sexual behavior as they have accepted their attraction towards same sex. Conclusion: There is a need to include concepts of sexuality in education curriculum and sensitize parents also and counseling of those exposed to homosexuality at a tender age is imperative.